26 songs in 30 days : Woody Guthrie's Columbia River songs and the planned promise land in the Pacific Northwest - Vandy, Greg (Sasquatch Books, 2016)
"Timed to celebrate the 75th anniversary of his employment by the federal government, KEXP DJ Greg Vandy takes readers inside the unusual partnership between one of America's great folk artists and the federal government, and shows how the first American folk revival of the 1930's was a response to hard times. The new book 26 Songs In 30 Days plunges deeply into the historical context of the time and the progressive politics that embraced Social Democracy during an era in which the United States severely suffered from The Great Depression." --